Hepatic Gene Expression Profiles Differentiate Steatotic and Non-steatotic Grafts in Liver Transplant Recipients - Šeda, Ondrej; Cahová, Monika; Míková, Irena; Šedová, Lucie; Daňková, Helena; Heczková, Marie; Brátová, Miriam; Ďásková, Nikola; Erhartová, Denisa; Čapek, Václav; Chylíková, Blanka; Trunečka, Pavel (Frontiers in Endocrinology, 2019)
Background: Liver transplantation leads to non-alcoholic liver disease or non-alcoholic steatohepatitis in up to 40% of graft recipients. The aim of our study was to assess transcriptomic profiles of liver grafts and to contrast the hepatic gene expression between the patients after transplantation with vs. without graft steatosis. Methods: Total RNA was isolated from liver graft biopsies of 91 recipients. Clinical characteristics were compared between steatotic (n=48) and control (n=43) samples. Their transcriptomic profiles were assessed using Affymetrix HuGene2.1ST Array Strips processed in Affymetrix GeneAtlas. Data were analyzed using Partek Genomics Suite 6.6 and Ingenuity Pathway Analysis. Results: The individuals with hepatic steatosis showed higher indices of obesity including weight, waist circumference or BMI but the two groups were comparable in measures of insulin sensitivity and cholesterol concentrations. We have identified 747 transcripts (326 upregulated and 421 downregulated in steatotic samples compared to controls) significantly differentially expressed between grafts with vs. those without steatosis. Among the most downregulated genes in steatotic samples were P4HA1, IGF1 or fetuin B while the most upregulated were PLIN1 and ME1. Most influential upstream regulators included HNF1A, RXRA and FXR. The metabolic pathways dysregulated in steatotic liver grafts comprised blood coagulation, bile acid synthesis and transport, cell redox homeostasis, lipid and cholesterol metabolism, epithelial adherence junction signaling, amino acid metabolism, AMPK and glucagon signalling, transmethylation reactions and inflammation-related pathways. The derived mechanistic network underlying major transcriptome differences between steatotic samples and controls featured PPARA and SERPINE1 as main nodes. Conclusions: While there is certain overlap between the results of current study and published transcriptomic profiles of non-transplanted livers with steatosis, we have identified discrete characteristics of non-alcoholic fatty liver disease in liver grafts potentially utilizable for establishment of predictive signature.